Immunoglobulin heavy chain enhancer is located near or in an initiation zone of chromosomal DNA replication. - Ariizumi, K (1993)
In several animal viruses, enhancers have been implicated in both DNA replication and transcriptional activation. The linkage of the two mechanisms appears intimate, in that common DNA binding factors can be shared. The immunoglobulin heavy chain (Igh) intronic [heavy chain joining region (JH)-mu chain constant region (C mu)] enhancer (E mu) is required for tissue-specific transcription of Igh genes and is essential for somatic recombination of diversity (D) and J segments. We show here that E mu is located at or near an origin of chromosomal DNA replication, which is more active in B lymphocytes than fibroblasts. E mu does not fulfill two criteria demonstrated for some cellular origins. E mu can initiate but not maintain autonomous replicating activity in B cells. E mu is unable to impart early replication timing to a transfected VDJ-C mu Igh locus in B cells. Instead we propose that E mu-associated ori activity contributes to tissue-specific Igh expression through local effects on chromatin structure leading to subsequent accessibility of transcription and/or recombination factors for the enhancer.